Il territorio bene comune (2012)
The central theme of this book is ecological and territorialist conversion as a strategic response to the crisis. 'The return to the territory' can be conceived as a valorisation of the common heritage of assets (environmental, urban fabric, landscape, socio-cultural) that mould the identity and lifestyles of every place on the earth. This calls for several issues to be addressed: the fusing of fragmented knowledge into a science of the territory that addresses the problems of socio-territorial and environmental decay in an integrated manner; the definition of new markers and policies of public welfare and happiness, including the landscape as a measure of the quality of peoples' life-worlds; the boosting of tools of local democracy and supportive federalism; the restoration of centrality to the rural world in the production of healthy food, hydro-geological protection measures, ecological reclamation, urban and landscape quality and integrated economies.